Reassessing the atomic size effect on glass forming ability: Effect of atomic size difference on thermodynamics and kinetics. (February 2016) - Han, Hyung-Seop; Park, Nayoung; Suh, Jin-Yoo; Nam, Ho-Seok; Seok, Hyun-Kwang; Kim, Won Tae; Kim, Yu-Chan; Cha, Pil-Ryung
Abstract: Glass forming ability (GFA) for some alloys may be difficult to explain in kinetic point of view alone and the thermodynamics must be considered as an important factor. Herein, investigation of the atomic size effect on the glass forming ability based on the molecular dynamics simulations for binary alloys with Lennard-Jones Embedded Atom Method potentials have been performed. The findings from this study showed that the size effect is accompanied by the change of phase diagram from solid solution to eutectic and change in the local stress/internal energy, which could contributes more to GFA than the kinetic factors such as efficient packing and resulting sluggish atomic transport. Highlights: We identify the origin of glass forming ability enhanced by atomic size difference. We examine changes by quantitatively separating the kinetic and thermodynamic contributions. Larger atomic size differences are found to improve glass forming ability. Role of atomic size difference is not necessarily to promote kinetic suppression through effective packing. Atomic size difference could influence GFA by introducing local strains.